Family Nogodinidae (Hemiptera: Fulgoroidea) from the Canary Islands, with the description of a new species of the genus Morsina Melichar, 1902 - Gnezdilov, Vladimir M.; López, Heriberto; Suárez, Daniel (Zootaxa, 2023)
Planthopper family Nogodinidae is recorded for the first time from the Canary Islands after a new species, Morsina gomerae sp. nov., described from the dry landscapes of La Gomera island. Mikewilsonia Holzinger, 2019 is placed in synonymy under Morsina Melichar, 1902. Mikewilsonia kunzi Holzinger, 2019 is transferred to Morsina with a new combination proposed—Morsina kunzi (Holzinger, 2019), comb. nov.